Deposition of Electroless Nickel Boron as Printed Circuit Board Surface Finish - Hardinnawirda, Kahar; Zetty Akhtar, Abd Malek; Siti Rabiatull Aisha, Idris; M., Ishak (Trans Tech Publications, Switzerland, 2016)
Electroless Nickel Boron had been appointed as potential coating in several applications in industry like aeronatics, petrochemical industry, electronics and firearms due to its desirable physical and mechanical properties such as high wear resistance and high hardness including provides uniformity in coating thickness. However, in semiconductor sector, the usage of Nickel Boron as coating layer still insufficient due to lack of study in term of its potential as coating on printed circuit board. This study aims to investigate the mechanical and physical properties of electroless Nickel Boron as potential printed circuit board coating layer. The study conducted by cutting Copper substrates to 50mm x 7mm x 1.5mm and then subjected to surface pre-treatment before soak in Nickel Boron plating bath solution that contain of different concentration of Sodium Borohydrate (NaBH4), 0.4, 0.6,0.8,1.0 and 1.2 g/l. Surface roughness was evaluated using 3D Roughness Reconstruction software. For mechanical properties, the hardness test was conducted by using Vickers Hardness Test MMT-X7 Matsuzawa and surface structure was evaluate using ProgRes C3 IM7200 Optical Microscope and Field Emission Scanning Electron Microscopy (FESEM). It was found that the surface roughness and hardness resistance were affected by Sodium Borohydrate (NaBH4) that correlate with the surface microstructure